Studying for Introductory Psychology: Differences Across Technical College, 2-, and 4-Year Institutions. (October 2019) - McCann, Lee I.; Ebert, Alexandria R.; Oechsner, Markus; Immel, Kathy R.; Kadah-Ammeter, Tammy L.
Three hundred thirty-three Introductory Psychology (IP) students from a 4-year university, 2-year community college, and a technical college provided survey data. Student self-reports significantly differed across schools on hours studied during exam weeks, textbook helpfulness, importance of lecture and class activities, quality and importance of course notes, and credit load. University students reported higher means on all of these, followed by 2-year and then technical college students. Students significantly differed on hours worked per week and current course grade, with technical college students having the highest means, followed by 2-year and then university students. There were a number of significant intercorrelations among the variables, some differing by institutional type. These institutional differences suggest that IP instructors may wish to consider these differences as they prepare to teach this course.